Detection of Eumonospora henryae (Apicomplexa: Sarcocystidae) from Falco columbarius (Falconiformes: Aves): Comparison of host–parasite phylogram and comments on the family Sarcocystidae Poche, 1913. (April 2021) - Chou, Shyun; Izawa, Nobumoto; Ike, Kazunori; Tokiwa, Toshihiro
Abstract: The genus Eumonospora Allen, 1933 (Apicomplexa: Sarcocystidae), an avian coccidia, is characterized by monosporocystic and octasporozoic oocysts without Stieda and substieda bodies. Some members of Eumonospora, which infect several raptor species, exhibit high levels of pathogenicity, making eumonosporiosis the leading cause of death in captive-bred raptors. The host specificity of these species appears to be mesostenoxenous, as evidenced by unsuccessful transmission between different orders of avian hosts. However, several studies have detected Eumonospora spp. in taxonomically distant avian hosts, indicating that some of these species may be euryxenous. In the current study, diarrheic fecal examination of a captive-bred juvenile merlin (Falconiformes: Aves) in Tokyo, Japan, was conducted, and a large number of oocysts were morphologically and molecularly identified as E. henryae (Yakimoff and Matschulsky, 1932), a coccidia species reported only in Strigiformes. This is a new recorded host for this coccidia. Phylogenetic analyses via Bayesian inference and maximum likelihood methods using concatenated genomic datasets consisting of nuclear 18S rDNA, nuclear 28S rDNA and mitochondrial cytochrome C oxidase subunit 1 gene, revealed a well-supported monophyletic clade of Eumonospora spp. belonging to the family Sarcocystidae Poche 1913, which largely corresponded to the avian host phylogram. Therefore, based on distinguishable oocyst morphology, a new subfamily, Eumonosporinae, within the family Sarcocystidae, is proposed, and a reconsideration of the definition of Sarcocystidae is suggested. Further molecular characterization of this emerging pathogen, as well as clarification of its complete life cycle, including cyst-forming ability, is required for more appropriate generic assessment. Graphical abstract: Image 1 Highlights: Eumonospora henryae, reported only from owls, is detected from Falco columbarius. New host record for this monosporocystic and octasporozoic species. Indicates broad host spectrum which across family boundary. Monophyletic Eumonospora spp. (Sarcocystidae) clade was found in phylogenetic study. A new sub-family, Eumonosporinae, is proposed based on oocyst morphology.